PENINGKATAN HASIL BELAJAR PENDIDIKAN AGAMA ISALAM MELALUI PENERAPAN METODE ROLE PLAYING PADA SISWA KELAS V DI SDN 295 PINRANG - Ishak, Ishak (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The main objective of this study is to find out the improvement of PAI learning results through the application of role playing methods to students of the V class in SDN 295 Pinrang. The type of method used in this study is Classroom Action Research which is an action research conducted with the aim of improving the quality of learning practice in the classroom. The technique of data collection in research is by observing the learning process, conducting interviews, making field records, observation sheets, documentation, and summarizing the value of learning results obtained by students from the test at the end of each cycle. The data analysis used is the process of systematically searching for and organizing the data obtained. The results of the study show that the learning outcomes of students from Cycle I to Cycle II have improved. The lowest score a student obtains at the time of the pretest is 40. While the lowest grade a student gets at the postest is 70. The highest score on the preteste is 85, while the highest point on the posttest is 100. It can be seen that almost all children have improved in learning and have passed the KKM score. For the learning outcomes of Cycle II obtained an average N-Gain 0.77 (high category) greater than the average N -Gain outcome of the Cycle I is 0.29, this means the ability of students in applying active learning Role Playing method used has been much improved compared to the cycle I and the learning result achieved becomes more effective.